2015
DOI: 10.1002/jsfa.7120
|View full text |Cite
|
Sign up to set email alerts
|

Comparative analysis of resistance gene analogues encoding NBS‐LRR domains in cotton

Abstract: The allotetraploid genome of cotton, after separating from its diploid parents, experienced polyploidisation, natural and artificial selection, hybrid necrosis, duplication and recombination which became the reason to shed off and evolve new genes for its survival. These driving forces influenced the development of genomic architecture that make it susceptible to diseases and pathogens as compared to donor parents.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 39 publications
1
14
0
Order By: Relevance
“…We assume that recent episodes of positive selection events have been occurred, overlapping similar more ancient events among these RGAs. Constantly with our results, similar existences of positive selective pressures acting on plant RGAs have been recently reported (Khan et al 2015;Perazzolli et al 2014). Finally, using the CODEMLSITES program and various selection models, we tested whether positive selection was acting at individual amino acid sites.…”
Section: Resultssupporting
confidence: 85%
“…We assume that recent episodes of positive selection events have been occurred, overlapping similar more ancient events among these RGAs. Constantly with our results, similar existences of positive selective pressures acting on plant RGAs have been recently reported (Khan et al 2015;Perazzolli et al 2014). Finally, using the CODEMLSITES program and various selection models, we tested whether positive selection was acting at individual amino acid sites.…”
Section: Resultssupporting
confidence: 85%
“…Comparative analyses among Rosaceae trees species regarding their resistance (R) genes have revealed that solvent-exposed residues of the LRRs domains are hyper-variable, with intensive positive selective pressures acting on them (Perazzolli et al, 2014). Similar results were constantly observed in a range of plant species (Li et al, 2010;Zambounis et al, 2012;Yang et al, 2013;Khan et al, 2015). We hypothesize that these positive selective pressures acting upon LRRs of the LRR-RSTK subfamily in M. notabilis might being associated mainly with a continual selective demand for their functional diversification in terms of increasing fungal disease resistance.…”
Section: Discussionmentioning
confidence: 66%
“…Our findings postulate also that LRRs of LRR-RSTKs exhibit signs of positive selection. Such a selective mode is promoting a rapid alteration of gene sequences in different alleles or species by a non-directional mode without altering the main functions, which in cases of fungal attacks, often increases the reservoir of the ligands that can be recognized in these interactions (Delph and Kelly, 2014).Positive selection on NBS-containing gene families in plants and especially among their LRRs domains, were reported in various studies Perazzolli et al, 2014;Khan et al, 2015), supporting the view that selection upon them for durable disease resistance might be a crucial component of nearly all plant breeding programs (Mace et al, 2014). Comparative analyses among Rosaceae trees species regarding their resistance (R) genes have revealed that solvent-exposed residues of the LRRs domains are hyper-variable, with intensive positive selective pressures acting on them (Perazzolli et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations